Dual axis solar tracking system - Kumar, Mugachintala Dilip; Kumar, Tenugu Manish; Akshay, Kongari; Kumar, Sowdapuram Yashwanth; Vikas, Udutha (International Journal of Applied Power Engineering (IJAPE), 2023)
Now a days, many people use solar photovoltaic systems since they generate efficient and clean energy. Polycrystalline and monocrystalline silicon modules are currently the most widely used products in the solar industry. Aside from possessing a flawless lattice structure, a high level of material purity, a low grain boundary energy, a weak internal resistance, and a high level of efficiency, monocrystalline silicon cells also have a uniform colour and a lack of spots, which contribute to its good aesthetic appeal. By placing the solar panels at the precise angle and direction specified by the motion of the sun, the system's efficiency can be increased. The solar tracking system for this research project uses LDR sensors that are connected to a microcontroller to track the sun's horizontal and vertical axes, while DHT11 and rain sensors are used to track the weather. This study offers a method for repositioning a solar array so that it faces the sun at all times. Since solar modules effectively convert sunlight into electricity, they are helpful solutions to the problem of power generation in remote areas. A microprocessor is used in the construction of such a system to operate a motor and sensor.